2005
DOI: 10.1086/432542
|View full text |Cite
|
Sign up to set email alerts
|

Bright X‐Ray Flares in Orion Young Stars from COUP: Evidence for Star‐Disk Magnetic Fields?

Abstract: We have analyzed a number of intense X-ray flares observed in the Chandra Orion Ultradeep Project (COUP), a 13 day observation of the Orion Nebula Cluster (ONC), concentrating on the events with the highest statistics (in terms of photon flux and event duration). Analysis of the flare decay allows to determine the physical parameters of the flaring structure, particularly its size and (using the peak temperature and emission measure of the event) the peak density, pressure, and minimum confining magnetic field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

62
418
2
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 269 publications
(484 citation statements)
references
References 42 publications
(84 reference statements)
62
418
2
2
Order By: Relevance
“…To explain the observed long-lasting fluorescent emission, the electron acceleration mechanism should be sustained over several days. While we have no detailed physical mechanism to propose for this, we note that many of the long-lasting flares observed in YSOs by Favata et al (2005a) require sustained heating of the flaring material to explain the observed duration of the events, which in some cases lasted a few days. The thermodynamic cooling time of the flaring plasma would be much shorter; therefore, to explain the observed long flaring events in YSOs, magnetic reconnection must be ongoing, on time scales of days, similar to what is observed for the Fe 6.4 keV fluorescent emission from Elias 29.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…To explain the observed long-lasting fluorescent emission, the electron acceleration mechanism should be sustained over several days. While we have no detailed physical mechanism to propose for this, we note that many of the long-lasting flares observed in YSOs by Favata et al (2005a) require sustained heating of the flaring material to explain the observed duration of the events, which in some cases lasted a few days. The thermodynamic cooling time of the flaring plasma would be much shorter; therefore, to explain the observed long flaring events in YSOs, magnetic reconnection must be ongoing, on time scales of days, similar to what is observed for the Fe 6.4 keV fluorescent emission from Elias 29.…”
Section: Discussionmentioning
confidence: 91%
“…Calvet & Hartmann 1992). The observation of very intense long-duration flares in YSOs, which implies flaring loop lengths of tens of stellar radii (Favata et al 2005a), provides evidence of flaring associated to these accretion streams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some COUP (Chandra Orion Ultra-deep Project) sources have revealed strong flares that were related to peculiar gigantic magnetic loops linking the magnetosphere of the central star with the inner region of the accretion disk. It has been argued that this X-ray emission could be due to magnetic reconnection in these gigantic loops (Favata et al 2005). In this section we examine this in more detail, investigating the role of magnetic reconnection events in the inner disc/corona of YSOs to explain the X-ray flares and check if magnetic reconnection may be related to the thermal jets of these sources.…”
Section: In the Context Of Ysosmentioning
confidence: 96%
“…In its form for time-tagged data, this algorithm was used for example to characterize the X-ray light curves of young pre-main sequence stars observed by the Chandra Orion Ultra-Deep Project (COUP, Getman et al 2005) in the Orion Nebula Cluster (ONC). A modified version of the S98 algorithm, based on a Maximum Likelihood rather than a Bayesian approach, was recently employed in other studies of stellar X-ray light curves (Wolk et al 2005;Favata et al 2005;Stelzer et al 2006). We will refer to this algorithm as the Maximum Likelihood Blocks (MLBs) and we introduce here a variant that is suitable for the analysis of binned light curves.…”
Section: Representation Of the Light Curve: Maximum Likelihood Blocksmentioning
confidence: 99%